Polymorphisms of Cytochromes P450 and Glutathione S-Transferases Synergistically Modulate Risk for Parkinson’s Disease - Fan, Hui-Hui; Li, Bao-Qing; Wu, Ke-Yun; Yan, Hai-Dan; Gu, Meng-Jie; Yao, Xing-Hao; Dong, Hao-Jia; Zhang, Xiong; Zhu, Jian-Hong (Frontiers in Aging Neuroscience, 2022)
Background: Environmental substances such as pesticides are well-known in link with Parkinson’s disease (PD) risk. Enzymes including cytochromes P450 (CYPs), esterases and glutathione S-transferases (GSTs) are responsible for the xenobiotic metabolism and may functionally compensate each other for subtypes in the same class. We hypothesize that the genetic effects of each class modulate PD risk stronger in a synergistic way than individually. Methods: We selected 14 polymorphic loci out of 13 genes which encode enzymes in the classes of CYP, esterase, and GST, and recruited a cohort of 1026 PD and control subjects from eastern China. The genotypes were identified using improved multiplex ligation detection reaction and analyzed using multiple models. Results: A total of 13 polymorphisms remained after Hardy-Weinberg equilibrium analysis. None of the polymorphisms were independently associated with PD risk after Bonferroni correction either by logistic regression or genetic models. In contrast, interaction analyses detected increased resistance to PD risk in individuals carrying the rs12441817/CC (CYP1A1) and rs2070676/GG+GC (CYP2E1) genotypes (P = 0.002, OR = 0.393, 95% CI = 0.216-0.715), or carrying the GSTM1-present, GSTT1-null, rs156697/AG+GG (GSTO2) and rs1695/AA (GSTP1) genotypes (P = 0.003, OR = 0.348, 95% CI = 0.171-0.706). The synergistic effect of GSTs on PD was primarily present in females (P = 0.003). No synergistic effect was observed within genotypes of esterases. Conclusions: We demonstrate a presence of synergistic but not individual impact on PD susceptibility in polymorphisms of CYPs and GSTs. The results indicate that the genetic interplay leads the way to PD development for xenobiotic metabolizing enzymes.